Effects of a high-intensity interval training program versus a moderate-intensity continuous training program on maximal oxygen uptake and blood pressure in healthy adults: study protocol for a randomized controlled trial (2016)
ABSTRACT: Background: Participation in aerobic exercise generates increased cardiorespiratory fitness, which results in a protective factor for cardiovascular disease and all-cause mortality. High-intensity interval training might cause higher increases in cardiorespiratory fitness in comparison with moderate-intensity continuous training; nevertheless, current evidence is not conclusive. To our knowledge, this is the first study to test the effect of high-intensity interval training with total load duration of 7.5 min per session. Methods: A randomized controlled trial will be performed on two groups of healthy, sedentary male volunteers (n = 44). The study protocol will include 24 exercise sessions, three times a week, including aerobic training on a treadmill and strength training exercises. The intervention group will perform 15 bouts of 30 s, each at an intensity between 90 % and 95 % of maximal heart rate. The control group will complete 40 min of continuous exercise, ranging between 65 % and 75 % of maximal heart rate. The primary outcome measure to be evaluated will be maximal oxygen uptake (VO2max), and systolic and diastolic blood pressure will be evaluated as secondary outcome measures. Waist circumference, body mass index, and body composition will also be evaluated. Discussion: Epidemiological evidence shows the link between VO2max and its association with chronic conditions that trigger CVD. Therefore, finding ways to improve VO2max and reduce blood pressure it is of vital importance to public health. Trial registration: NCT02288403. Registered on 4 November 2014.